From instrumentalization to commoning: A critical review of participation in urban nature-based solutions - Remme, Devyn; Haarstad, Håvard (Frontiers in Sustainable Cities, 2022)
Nature-based solutions (NBS) are becoming a widely recognized approach to urban sustainability. Most of the literature and policy handbooks on the topic emphasize the importance of participation in some form but interpretations and levels of commitment vary. While the mainstream discourse often presents NBS as a set of win-win solutions for urban sustainability, there is a tendency to romanticize both nature and participatory planning processes in the institutional language and practices of NBS. In this paper, we review critical perspectives on the mainstream NBS discourse. Then we bring scholarship concerning the relationship between cities, nature and social change into conversation with scholarship on commoning, to outline an approach for rethinking the democratic and transformative potential of NBS. In this approach, we argue for moving beyond the instrumentalization of nature inherent to mainstream NBS, and locate, within diverse strands of theory, perspectives that contribute to a vision of commoning as a frame for ecological spaces in cities. We contrast the tendency for instrumentalization and enclosure of NBS and urban space to the opportunities opened by the commoning approach, particularly in terms of equality of access, public and shared resources, and distribution of benefits.